The impact of english teachers’ education performed at the Federal University of Piauí: an analysis of the professional choices of some graduated students from the english language major - Rodrigues, Beatriz Gama (Universidade Estadual Paulista, 2019)
In this article, I present some narratives about professional choices from some graduates from the English Language Major from the Federal University of Piauí. In our program, we aim at educating English teachers able to fulfill the insufficiencies of professionals who are appropriately qualified to work in the municipal, state and private teaching networks of education in the state of Piauí, providing an educational service of good quality, based on a broader vision of foreign language, not only as a linguistic phenomenon, but as a tool that enables discursive engagement of its users, conceiving language as a social act or practice. In order to know the professional experiences of some of our graduates, I have elaborated some questions for them to reflect about their choices, challenges and delights. Some graduates selected were working in public and private schools, in the capital and in the interior of the State, to know a little more about their contexts and the reasons for their choices. We believe that these analyzes will help us to reflect also about the role our program has, and how we can help our students to prepare to become critical and competent professionals of languages teaching-learning.